The Relationship of Health Aid to Population Health Improvements - Bendavid, Eran (JAMA Intern Med, 2014)
IMPORTANCE: Foreign aid to the health sector is an important component of all health spending in many developing countries. The relationship between health aid and changes in population health among aid recipients remains unknown. OBJECTIVE: To quantify the relationship between health aid and changes in life expectancy and under-5 mortality among aid recipient nations. DESIGN: Cross-country panel data analysis of the relationship between longitudinal measures of health aid, life expectancy, and under-5 mortality. Using difference models for longitudinal data with fixed effects for countries and years, we estimate the unique relationship between health aid and changes in life expectancy and under-5 mortality, controlling for gross domestic product per capita, urbanization, and total fertility rate. SETTING AND PARTICIPANTS: 140 aid-recipient countries between 1974 and 2010. MAIN EXPOSURES AND OUTCOMES AND MEASURES: The main exposure is the annual amount of development assistance directed to the health sector in constant 2010 US dollars; the principal outcomes are the improvements in under-5 mortality and life expectancy in in the period following aid receipt. RESULTS: We find that between 1974 and 2010, life expectancy increased by 0.24 months faster (95% CI 0.02-0.46, p=0.03) and under-5 mortality declined by 0.14 per 1,000 live births faster (95% CI 0.02-0.26, p=0.02) with each 1% increase in health aid. We also find that the association between health aid and health improvements has been strengthening over time, with the closest association between 2000 and 2010. We find that health improvements associated with health aid are measurable for 3-5 years after aid disbursement. These findings imply that an increase of $1 billion in health aid could be associated with 364,800 (95% CI 98,400-630,000) fewer under-5 deaths. CONCLUSIONS: Foreign aid to the health sector is related to increasing life expectancy and declining under-5 mortality. The returns to aid appear to last for several years and have been greatest between 2000 and 2010, possibly because of improving health technologies or effective targeting of aid.